The Aztecs - Spilsbury, Louise (Spilsbury, Louise. Analyze the ancients., 2019)
Explores the ancient Aztec civilization, discussing its society, beliefs, work and trade, warriors, and everyday life. Includes color illustrations, a glossary, and further resources.